1999
DOI: 10.1016/s0741-5214(99)70279-x
|View full text |Cite
|
Sign up to set email alerts
|

The diameter of the common femoral artery in healthy human: Influence of sex, age, and body size

Abstract: The diameter of the CFA increases with age, initially during growth but also in adults. This is related to age, body size, and sex male subjects have larger arteries than female subjects. It is now possible to predict the normal CFA diameter, and nomograms that may be used in the study of aneurysmal disease are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
9
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(162 citation statements)
references
References 17 publications
6
143
9
1
Order By: Relevance
“…11). The observed diameter of 0.4-0.5 mms conforms to average 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 values of intact femoral arteries vessels in the living (Sandgren et al, 1999). Therefore, it seems plausible to identify them as calcifications of the femoral artery.…”
Section: Discussionsupporting
confidence: 80%
“…11). The observed diameter of 0.4-0.5 mms conforms to average 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 values of intact femoral arteries vessels in the living (Sandgren et al, 1999). Therefore, it seems plausible to identify them as calcifications of the femoral artery.…”
Section: Discussionsupporting
confidence: 80%
“…43 Safe arterial access may be more challenging in women: studies have shown that women have smaller and shorter CFA compared with men 44 (Figure 7). Measures of height and weight correlate with CFA size.…”
Section: Sex Anatomy and Bmimentioning
confidence: 99%
“…This age-dependent increase in aortic diameter is accompanied by a compensatory increase in wall thickness to minimize the increase in circumferential wall stress, but the compensatory response is greater in women than in men. 42 Other arteries, including the common femoral artery, are smaller in women, 43 which may affect suitability for endovascular repair in the presence of an AAA (see below). At any age, healthy men also have stiffer aortas than women, but this may not be independent of the lower aortic diameters in women.…”
Section: Biological and Anatomic Factors Influencing Aaa Developmentmentioning
confidence: 99%
“…71,72 In a study of 704 cases (98 women) from the Cleveland Clinic, graft limb occlusions were significantly more common in women (11% versus 3.3%; Pϭ0.022). 73 The problems relate not only to smaller access vessels 43 but also to shorter, wider, and more angulated aneurysm necks and possibly a greater likelihood of suprarenal involvement. 46,47,74 Nevertheless, the case fatality, endoleak, and late reintervention rates are similar for men and women.…”
Section: Gender and Treatmentmentioning
confidence: 99%